2006
DOI: 10.3341/kjo.2006.20.1.70
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Alveolar Rhabdomyosarcoma of the Ethmoid Sinus Invading the Orbit in an Adult

Abstract: PurposeA case study and literature review of alveolar rhabdomyosarcoma (RMS) in an adult.MethodsA 48-year-old male patient presented at our clinic complaining of proptosis that had persisted for 2 weeks in his left eye. A computed tomography (CT) scan revealed a destructive soft-tissue mass in the left ethmoid sinus with invasion of the left orbit and compression of the medial rectus muscle. Endoscopic intranasal biopsy revealed alveolar RMS. Conservative debulking and orbital wall decompression were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
(29 reference statements)
0
25
0
1
Order By: Relevance
“…It is a common soft-tissue malignancy in children and adolescents but infrequent in adults. 1 The orbit is the primary site in approximately 10% of children with RMS 2,4 , and in adults orbital involvement is very rare. 2 The histopathologic types of RMS include embryonal, alveolar, pleomorphic and botryoide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a common soft-tissue malignancy in children and adolescents but infrequent in adults. 1 The orbit is the primary site in approximately 10% of children with RMS 2,4 , and in adults orbital involvement is very rare. 2 The histopathologic types of RMS include embryonal, alveolar, pleomorphic and botryoide.…”
Section: Discussionmentioning
confidence: 99%
“…1 The orbit is the primary site in approximately 10% of children with RMS 2,4 , and in adults orbital involvement is very rare. 2 The histopathologic types of RMS include embryonal, alveolar, pleomorphic and botryoide. Alveolar RMS is an aggressive subtype with a distinct histology, characterized by small round cells and with a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moon et al, described a patient with alveolar RMS of the ethmoid sinus with extending to the orbit and cervical lymph node involvement, who was treated with surgery and chemoradiotherapy, but died after seven months because of metastasis that progressed to the spine [2]. Similarly, Torres-Peña et al, described two adults with alveolar RMS, one patient showed the involvement of ethmoid sinus and right orbit; in the other patient the mass was centered at the nasal cavity and infiltrated the orbit and the ethmoidal and frontal sinuses [3].…”
Section: Discussionmentioning
confidence: 99%
“…While some cases of alveolar RMS have been described in young adults, the occurrence of this neoplasm in adults over the age of 45 years is extremely uncommon, being pleomorphic RMS, characterized by different microscopic features and biological behavior, the most common histotype in this category of patients [8][9][10]16]. For this reason, the inclusion of alveolar RMS in the differential diagnosis of small round cell tumors of the head and neck region is often neglected.…”
Section: Discussionmentioning
confidence: 99%